Impact of Bilingualism on Learning English as Second Language for English Proficiency Students: A Case Study of Tangaza University Foreign Students - Ebubeogu, Mercy Chikaodili; Kabare, Timothy Peter (International Journal of Linguistics, 2025)
Purpose: This research investigated the impact of bilingualism on the acquisition of English as a second language (ESL) among students seeking English proficiency. The primary objectives of the study was to examine the effects of bilingualism on the ESL learning process, identify recurring language transfer patterns resulting from bilingualism in learning ESL and determine effective bilingual strategies for optimizing ESL learning. Methodology: The research questions guiding the study were: How does bilingualism influence the ESL learning process? What language patterns are transferred due to bilingualism in ESL learning? And what bilingual strategies can enhance ESL learning? The study adopted a qualitative approach, utilizing a case study design to investigate the experiences of English proficiency students at Tangaza University. Convenient sampling methods were employed, and data was collected through structured questionnaires and written compositions on the topic How I Spent My Last Holiday. The collected data was analyzed using thematic and content analysis. Findings: The study findings revealed that bilingualism influenced ESL learning in both positive and negative ways, with recurring language transfer patterns at phonological, morphological, syntactic, and grammatical levels. Effective bilingual strategies, such as consistent practice, immersion, and the use of technological tools, were identified as key to enhancing ESL learning outcomes. Unique Contribution to Theory, Practice and Policy: The study was guided by Larry Selinker’s Language transfer theory (1972), which significantly influenced the field of second language acquisition (SLA). The study recommended more effective teaching methodologies, including tailored instructions, structured writing training, and interactive learning activities, to improve learners’ language interaction and usage.